openVFIFE: An Object-Oriented Structure Analysis Platform Based on Vector Form Intrinsic Finite Element Method - Biao Tan (MDPI AG, 2021)
The vector form intrinsic finite (VFIFE) method is a new and promising structural analysis technique that has many advantages as compared with the conventional finite element method (FEM) in analyzing the complex behaviors of a structure. However, despite the popularization of its application in civil and infrastructure engineering, there is no available unified general analysis framework for it, which limits the applications and developments of VFIFE. This work develops and implements a platform (termed openVFIFE) based on a new proposed object-oriented framework to facilitate the development and application of the vector form intrinsic finite method as well as the efficient and accurate analyses of complex behaviors for civil structures. To validate the platform, a series of numerical examples are conducted. Furthermore, to extend the applications of VFIFE, the nonlinear dynamic and collapse processes of a transmission tower under earthquake load are studied using openVFIFE. The results of these numerical examples simulated by the developed truss or beam elements are consistent with theoretical solutions, previous research or conventional finite element models. The failure modes of the transmission tower under earthquake load simulated by the platform is consistent with those observed in real cases. In addition, the results of nonlinear dynamic analyses of the transmission tower show that the computational efficiency of the proposed platform is 6-10 times higher than that of the conventional finite element method. The results provide sufficient evidence to prove the accuracy and efficiency of the proposed platform in the static, dynamic and elastoplastic analyses of truss and frame structures, especially in the structure analysis characterized by strong geometry nonlinearity. It is noteworthy that in addition to the link and beam elements, further work is undergoing on implementing more elements, such as shell and solid elements. The openVFIFE also allows researchers who are interested in this topic to put their creative ideas into this platform and continuously improve the completeness and applicability of the VFIFE method.